The meaning of manufacturing flexibility as perceived by Malaysian Manufacturing Practitioners - Mohd Ghazali, Maarof; Gusman, Nawanir; Muhammad Fakhrul, Yusuf (Asian Scholars Network, 2022)
As businesses are facing intense global challenges, they are forced to become more dynamic and innovative. This requires firms the need to act fast and make dramatic changes to meet the customer and market demands. To respond, manufacturers are seeking ways to enhance their competitiveness through manufacturing flexibility strategy to enable them to become more resilient in overcoming market uncertainty and changing customers preferences. However, current research on manufacturing flexibility is still lacking on defining the multidimensional nature of flexibility itself. Therefore, this research intends to further explore the suitable meaning of manufacturing flexibility by looking at the past literature as well as the inputs from the industry practitioners in Malaysia. A qualitative research approach has been used to gather data by interviewing seven industry practitioners who works in various industry sectors in Malaysia. Subsequently a literature review has been done to get some understanding of what past researchers have mentioned about manufacturing flexibility. The result of this research points out that manufacturing flexibility relates to the ability of the organization to utilize its internal resources effectively and efficiently to produce variety of products or services that can meet various customers’ requests regardless of the environmental uncertainty with minimum effect to the overall cost and objective.